2022
DOI: 10.1186/s12957-022-02759-z
|View full text |Cite
|
Sign up to set email alerts
|

An effective method to reduce lymphatic drainage post-lateral cervical lymph node dissection of differentiated thyroid cancer: a retrospective analysis

Abstract: Background Lymph or chyle leak (LL/CL) is severe complications after lateral cervical lymph node dissection (LLND), mainly due to iatrogenic injury of the lymphatic duct. Efficient and well-operated methods to reduce postoperative drainage are still lacking. This was a feasibility study to evaluate a new method of preventing LL/CL compared to conventional treatment. Method We retrospectively analyzed 20 consecutive patients who used the “pedicled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Similarly, the omohyoid muscle can be used by severing its hyoid attachment. Zhang et al 69 used an omohyoid-based flap to cover the level IV region and reinforced this flap with non-absorbable sutures to the surrounding soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the omohyoid muscle can be used by severing its hyoid attachment. Zhang et al 69 used an omohyoid-based flap to cover the level IV region and reinforced this flap with non-absorbable sutures to the surrounding soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies reported chylothorax following endoscopic lung or esophageal cancer resection using certain energy devices; therefore, such devices are not completely reliable [ 13 , 14 ]. Zhang et al [ 15 ] recently reported the usefulness of pedicled omohyoid flap coverings in preventing postoperative lymph node or chyle leakage. However, their study enrolled only a few patients, and the procedure was complicated.…”
Section: Discussionmentioning
confidence: 99%
“…However, their study enrolled only a few patients, and the procedure was complicated. Thus, the generalizability of the findings is questionable [ 15 ]. As mentioned above, no effective chyle prevention method has yet been established.…”
Section: Discussionmentioning
confidence: 99%